Economic Implications Under Cross-Strait Exchanges -Take Taiwanese College Students as an Example - Yen, Yang-Ching; Chang, Chih-Hsiung; Tien, Jui-Chu; Shen, Shih-Chi; Chang, Heidi H (International Journal of Asian Social Science, 2019)
In the current development of cross-strait relations, Taiwanese college students are undoubtedly the most important ethnic group. In October 2015, at the Fifth Plenary Session of the 18th CPC Central Committee, the CPC proposed to deepen Cross-Strait economic cooperation in a mutually beneficial and win-win way and benefit more ordinary Taiwanese young people as well as the small and medium-sized enterprises. In 2017, Yu Zheng Sheng, chairman of the Mainland Political Consultative Conference, mentioned at the CPPCC National Committee meeting: "we will strengthen exchanges with Taiwan’s grassroots people and young generations and build a solid foundation for the peaceful development of Cross-Strait relations". We can see that the fight for the goodwill and recognition of young people toward Mainland will remain the top priority of Mainland China s work on Taiwan. To win the recognition of Taiwanese youth for the Mainland has actually been implemented for years. In the past, Taiwanese students were invited to visit and explore Mainland China in summer and winter vocations, expected to enhance their feelings towards Chinese people and promote their recognition of the Mainland China. With the gradual opening up of Cross-Strait policies and the wide-and-deep exchange of views, the concrete result has become the focus of common concern across the Taiwan Strait. The empirical results from the questionnaire survey in this study explain the specific impact of Cross-Strait exchange on Taiwanese students. In particular, the study has indeed demonstrated its significant impact on many aspects of the college students’ career and entrepreneurial awareness and willingness propositions.